Delirio postoperatorio y características quirúrgicas de pacientes sometidos a anestesia general en cirugías electivas en el Hospital Regional de Loreto, 2021 - Huamani Cardenas, Hilarion (2022)
Postoperative delirium is a relevant and prevalent entity with an incidence of 70%. It is mainly associated with surgeries in older adult patients, with previous cognitive alterations. As well as long-term surgeries such as hip surgery. POD is characterized by transient cognitive impairment, motor and sleep disturbances. POD is more common in female patients undergoing abdominal surgery, expanding the factors associated with POD so far described in the international and national literature. Postoperative cognitive alterations involve cognitive deficits, an increase in postoperative hospitalization days, high surgical costs and higher mortality. In the appearance of POD, etiopathogenic mechanisms such as alterations in brain perfusion and an inappropriate inflammatory response induced by anesthetics have been described. In addition to Postoperative Cognitive Disorder (PCPO) it is as a consequence of inflammatory alterations at the brain level and its relationship with late complications such as dementia and increased mortality and that are still under investigation. the appearance of POD has also been described frequently related to the type of anesthesia, surgery; and patients with previous cognitive alterations that were not identified in the preoperative period and chronic diseases, these are associated with chronic complications. Regarding treatment, nonpharmacological treatment and the use of neuroleptics have been proposed; and emphasizing the implementation of prevention and diagnostic actions6. The treatment of choice are analgesics and anxiolytics, however, it is necessary to apply standardized protocols for preoperative diagnosis, management and follow-up of patients with postoperative cognitive dysfunction. Therefore, it is considered necessary to expand knowledge about the DPO in our regional context.